A vehicle for peacebuilding or cloak of impunity? The Zimbabwe National Peace and Reconciliation Commission (African Human Rights Yearbook / Annuaire Africain des Droits de l’Homme, 2022)
ABSTRACT:This article interrogates the efficacy of truth commissions as mechanisms for peacebuilding and reconciliation in Africa, with reference to Zimbabwe’s National Peace and Reconciliation Commission (NPRC). It questions the credibility and effectiveness of this institution in an attempt to establish whether the NPRC is a vehicle for peacebuilding or just a veil covering state impunity. Through a review of literature, the article explores the efficacy of the NPRC in comparison with the truth commissions established in Rwanda and South Africa. The article establishes that some of the challenges faced by the NPRC include a limited tenure, suppression of truth, limited institutional independence and resources, lack of political will, as well as usurpation of functions by the executive. Lessons identified from South Africa and Rwanda include adoption of diverse peacebuilding initiatives such as combining restorative justice with reparation, and provision of psychosocial care so as to achieve holistic reconciliation. In order to strengthen the capacity of the NPRC to usher in sustainable peace in Zimbabwe and enhance its credibility, the authors recommend extension of the tenure of the NPRC, truth-telling, cessation of state control and interference with operations of the NPRC, and adequate resourcing it. TITRE ET RÉSUMÉ EN FRANCAIS:Mécanisme de consolidation de la paix ou instrument d’impunité? La Commission nationale pour la paix et la réconciliation du ZimbabweRÉSUMÉ:Cet article questionne l’efficacité des «commissions vérité» en tant que mécanismes de consolidation de la paix et de réconciliation en Afrique avec un accent particulier sur la Commission nationale pour la paix et la réconciliation du Zimbabwe (NPRC). Il remet en question la crédibilité et l’efficacité de cette institution pour tenter de déterminer si le NPRC est un mécanisme de consolidation de la paix ou simplement un voile couvrant l’impunité de l'État. À travers une revue de la littérature, l’article explore l’efficacité du NPRC en comparaison avec les commissions vérité établies au Rwanda et en Afrique du Sud. L’article établit que certains des défis auxquels le NPRC est confronté comprennent un mandat limité, la suppression de la vérité, une indépendance institutionnelle et des ressources limitées, un manque de volonté politique, ainsi que l’usurpation de ses fonctions par l’exécutif. Les leçons identifiées de l’Afrique du Sud et du Rwanda comprennent l’adoption de diverses initiatives de consolidation de la paix telles que la combinaison de la justice restauratrices et la réparation, ainsi que la fourniture de soins psychosociaux afin de parvenir à une réconciliation holistique. Afin de renforcer la capacité du NPRC à impulser une paix durable au Zimbabwe et d’améliorer sa crédibilité, les auteurs recommandent l’extension du mandat du NPRC, la révélation de la vérité, la cessation du contrôle de l’État et l’interférence avec les opérations du NPRC, et de la ressourcer.
Keywords: Truth and Reconciliation Commissions; Zimbabwe; efficacy; peacebuilding; sustainable peace